Solução estrutural para a segurança do suprimento de energia elétrica no estado do Amazonas - FROTA, Willamy Moreira (Universidade Federal do Pará, 2016)
The electric energy vector assumes significant importance in the process of the Amazon integration to the national development. The electric energy support on this region, reaches a high priority level among the constitutional objectives on reduction the regional differences (FROTA, 2004). In the Amazon state, it can be stated that the lack of energy is a fact that decreases the regional development, and in many locations, smaller and more isolated, a factor of social, economic and cultural marginalization. The historical situation of the increasing use of fuel derived petroleum to the power generation in the Amazon state brings huge economic and environmental damage to the Brazilian society, and it has to be solved by the energetic Brazilian planning organ, by imposing the need of reaching other cleaner, safer and less expensive sources. The state is different from other regions of the country due to the existence of several isolated systems, mainly from its capital, Manaus, that shows low reliability and quality in its energy service, adding to that the high cost, considering the need of thermal diesel and oil generation, their amount represents about 73% of all fuel that have to be used in Brazil to thermoelectric power generation (GTON, 2009), having a final cost of 3 billions (US$ 1.5 billion) which is supported, most of it, by the sources transferences obtained through the subsidies of the Consumption Account of Fossil Fuels - CCC. Having this in mind, this assignment has as objective to present an approach of the mainly existing problems, as well as a proposal of structural solution for the energy business to the Amazon state, that can contribute to the improvement of the principles that rule, the compatible energetic politics with the goals of the updated institutional model of the Brazilian electric sector, giving birth to a new cycle of development and growing to the Amazon state and to the Amazon region.